A Qualitative Study on Mettā Practice in Conflict Management among Myanmar Buddhists - Kyi, Khin Maung (Journal of Media, Journalism & Mass Communication, 2025)
As there are many conflicts in daily life, Myanmar Buddhists are also facing some conflicts in their daily lives. When Myanmar Buddhists encounter conflicts in their daily lives, it is uncertain whether they can manage these issues using mettā (loving-kindness), despite frequently reciting the Metta Sutta and practicing mettā as they interpret it. This article examines the ways in which Myanmar Buddhists apply mettā (loving-kindness) to manage conflicts as part of their daily lives. The research examines the fundamental values of saddhā (faith), vīriya (effort), sati (mindfulness), paññā (wisdom), and sīla (morality) to understand how to develop and utilize mettā in effectively handling conflicts. The study aims to explore the mettā practice among Myanmar Buddhist people by raising awareness of the challenges and opportunities in applying mettā. A thorough study of the mettā practice is therefore essential if one is to completely investigate the effective mettā application (EMA).